2001
DOI: 10.1073/pnas.221467398
|View full text |Cite
|
Sign up to set email alerts
|

Using flexible loop mimetics to extend Φ-value analysis to secondary structure interactions

Abstract: Chemical synthesis allows the incorporation of nonnatural amino acids into proteins that may provide previously untried probes of their folding pathway and thermodynamic stability. We have used a flexible thioether linker as a loop mimetic in the human yes kinase-associated protein (YAP 65) WW domain, a three-stranded, 44-residue, ␤-sheet protein. This linkage avoids problems of incorporating sequences that constrain loops to the extent that they significantly change the nature of the denatured state with conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
76
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 36 publications
13
76
1
Order By: Relevance
“…Each such coordinate can be probed by ⌽, which ϭ ⌬⌬G ‡-D ͞⌬⌬G N-D for a prescribed mutation of a side chain or even backbone moiety (40,41). ⌽ effectively probes a local reaction coordinate based on Q i .…”
Section: ⌽ As An Index Of Local Reaction Coordinatesmentioning
confidence: 99%
“…Each such coordinate can be probed by ⌽, which ϭ ⌬⌬G ‡-D ͞⌬⌬G N-D for a prescribed mutation of a side chain or even backbone moiety (40,41). ⌽ effectively probes a local reaction coordinate based on Q i .…”
Section: ⌽ As An Index Of Local Reaction Coordinatesmentioning
confidence: 99%
“…WW domains have been used extensively in experimental and theoretical folding studies (1)(2)(3)(4)(12)(13)(14)(15)(16)(17)(18)(19). Traditional side-chain and amide-to-ester mutagenesis of Pin WW in conjunction with laser temperature-jump (T-jump) relaxation studies revealed that the folding rate was limited by nucleation at the loop 1 substructure (1)(2)(3)16), similar to the situation observed in SH3 domains (20,21).…”
mentioning
confidence: 97%
“…1N), has been shown to fold with biphasic kinetics exhibiting intermediates during folding (3,5,6,(11)(12)(13)(14)(15)(16). We address this problem here with the design of new FBP28 WW domain mutants and by examining their structural properties and folding kinetics.Because of the small size, fast folding kinetics, and biological importance, the formation of intermolecular β-sheets is thought to be a crucial event in the initiation and propagation of amyloid diseases, such as Alzheimer's disease, and spongiform encephalopathy, FBP28, and other WW domain proteins (e.g., Pin1 and FiP35) have been the subjects of extensive experimental (4,11,(17)(18)(19)(20)(21)(22)(23) and theoretical (3,5,6,(12)(13)(14)(15)(16)(24)(25)(26)(27) studies. However, a folding mechanism of the FBP28 was debatable for a long time because of its complexity.…”
mentioning
confidence: 99%